Herder’s Insights on the “Modern” Justification of War: A Teaching for the Present? - Ventura, Lorella (Filosofia Morale/Moral Philosophy, 2022)
In this paper I propose a reflection on Herder’s critique of the discourse of his time in Auch eine Philosophie der Geschichte (1774), focused on the narratives employed to justify war and the use of military force. Particularly relevant is the strict link between these narratives and the self-representation of Europe as “modern”. I will show that Herder’s insights may help understand the framework, pattern, and roots of the present arguments in favour of wars, and their acceptance.